Регіональна політика у сфері надрокористування та її суперечності в Україні - Міщенко, В.С. (Економіка природокористування і охорони довкілля, 2013)
Показано, що становлення регіональної політики надрокористування зіштовхується в Україні зі значними суперечностями. ЇЇ інституціональний розвиток носить поки фрагментарний характер, а фінансове підґрунтя залишається несформованим. Вирішення відповідних питань зосереджене у площині розширення повноважень регіонів щодо розпорядження мінеральними ресурсами місцевого значення. It is shown that regional mineral resource policy in Ukraine is in its infancy and faces significant contradictions. Its institutional development is still fragmentary, and financial basis remains unformed. In situations where the local level translates to meet the increasingly wide range of tasks efficiently use the potential of the local mineral resource base is updated and requires the development of tools for their resolution. Development regional Policy and filling with real content associated with the expansion of the powers of regions on local resource management and decentralization of appropriate data base (inventories deposits, balance stocks) and licensing procedures. The system of special permits for local minerals was at this time a significant inhibitory factor investment processes in the mineral resource use. It is expedient to transfer this process to the regional level. At the same time raises the question of substantial simplification of procedures for issuing permits, their differentiation for different groups of minerals. In this context requires a clear regulation without auction sale permits for mineral resource use, which applies to raw materials of local importance. Subject to decentralize access to information resources on the interiors. For this purpose, appropriate funds to create a system of geological information – sectoral and territorial (regional) – with open access to them mineral resource users regardless of ownership.